A cohort study of postnatal depression, infant feeding practices and infant growth in Male', the Republic of Maldives - Abdul Raheem, Raheema (Curtin University, 2014)
A cohort study was undertaken on 458 mothers and their infants, selected from antenatal clinics in Malé, the capital city of the Republic of Maldives. Details of infant feeding and growth and maternal perinatal depression were recorded. Breastfeeding initiation is 100%, but there is a high rate of prelacteal and early complementary feeds. Perinatal depression rates are similar to other regional countries, but commonly results in early cessation of breastfeeding.